Bunch compression study using the envelope model in CSRm - 殷达钰 刘勇 原有进 杨建成 李朋 梅立荣 柴伟平 张小虎 (Chinese physics C, 2012)
The feasibility of attaining a short-pulse-duration heavy ion beam with a nanosecond pulse length is studied in the main ring of the Heavy Ion Research Facility in Lanzhou （HIRFL）. Such a heavy ion beam can be produced by non-adiabatic compression, and it is implemented by fast rotation in the longitudinal phase space. In this paper, the possible beam parameters during longitudinal bunch compression are studied by using the envelope model. The result shows that a shortest heavy ion bunch 23Su2S＋ of 29 ns with energy of 200 MeV/u can be obtained, which can satisfy high energy density physics research.